Ensamble (2020)
Ensamble is a mixed- used building project that connects two neighborhoods, Río Negro and Los Andes. This is possible due to the increase in public space and the generation of a building with a mixture of non-traditional uses, taking hybrid architecture as a reference. Ensamble aims to reduce the unemployment rate of young people in extracurricular moments, involving them in activities that are related to art, technology and culture, to keep them away from criminal activities. In the same way, Ensamble seeks to serve as a reinforcement and training space for these young people in order to complement their education and thus avoid student desertion. The project seeks to create a meeting point between two different neighborhoods. Río Negro is characterized by a condition of low-middle income and informality, where mechanical workshops, small businesses and tenants predominate. The Los Andes neighborhood is characterized by a condition of upper-middle income where residential complexes predominate. Ensamble contains a complementary educational center, a multifunctional space that can serve as an auditorium or as a performing arts room, shops that activate the project, spaces for art, community housing for students and workshops that promote the trades of the Neighborhood. From the mix of uses, it is possible to generate active spaces, promote encounters, promote links and connections for a diverse population where there is activity during the day and at night.